만성 신부전 환자에서 부갑상샘 절제술 후 종격동에서 발견된 이소성 부갑상샘 1예 - 정덕은; Duk Eun Jung; 최지은; Jee Eun Choi; 이강원; Kang Won Lee; 이유민; Yu Min Lee; 이지은; Ji Eun Lee; 김현정; Hyun Jung Kim; et al. (Kidney research and clinical practice, 2009)
Hyperparathyroidism is one of the most serious complications for hemodialysis patients. Parathyroidectomy is indicated in patients with severe hyperparathyroidsm refractory to medical treatment. An 39-year-old man who were maintained by hemodialysis underwent parathyroidectomy due to tertiary hyperparathyroidism. The level of intact PTH fell after parathyroidectomy but subsequently rose. We checked up the parathyroid gland by MIBI scan and CT. As a result, a mass was found in the anterior mediastinum. So it is important to suspect the ectopic parathyroid gland when the PTH level elevation is persistent after parathyroidectomy in chronic renal failure patient.